1520. Respiratory Syncytial Virus Hospitalizations (RSVH) and All-Cause Bronchiolitis Hospitalizations (BH) Among Children Aged ≤ 24 Months at the Start of RSV Season With Bronchopulmonary Dysplasia/Chronic Lung Disease of Prematurity (BPD/CLDP) Before and After the 2014 American Academy of Pediatrics (AAP) Policy. (31st December 2020) - Fergie, Jaime; Gonzales, Tara; Suh, Mina; Jiang, Xiaohui; Fryzek, Jon; Howard, Ashley; Bloomfield, Adam
Abstract: Background: The AAP, in 2014, stopped endorsing palivizumab for use in children with BPD/CLDP born at < 32 weeks' gestational age (wGA) between the ages of 12 to 24 months not requiring medical support during the 6 months before the start of RSV season and all children with BPD/CLDP born at > 32 wGA. We sought to understand the impact of the guidance change on RSVH and BH in children no longer advised for RSV immunoprophylaxis with palivizumab. Methods: Children with BPD/CLDP aged ≤ 24 months at the RSV season start and hospitalized for RSV or bronchiolitis during the 2010-2017 RSV seasons (November-March) were studied. RSVH, BH, and BPD/CLDP were defined by International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) and ICD-10-CM codes. ICD-9 codes for wGA combine 31 and 32 wGA into one code. Therefore, for BPD/CLDP, we classified group 1 as children aged 12 to 24 months who were born at < 31 wGA and group 2 as those born at ≥ 31 wGA. The Children's Hospital Association's Pediatric Health Information System ® (PHIS) data set was used to describe frequency and characteristics of RSVH and BH and disease severity (including intensive care unit [ICU] admission and mechanical ventilation [MV]) before and after the 2014 AAP policy. Statistical analyses were done using z-tests; SAS version 9.4. Results: Among children with BPD/CLDP, RSVH rates were 1.7% (1035/59, 217) before 2014 and 2.1% (973/45, 470) after 2014 ( P < 0.0001). RSVH rose after the policy change vs before among children with BPD/CLDP in both group 1 (0.40% vs 0.26%; P < 0.0001) and group 2 (0.22% vs 0.14%; P =0.002). Similarly, BH also increased for both group 1 ( P < 0.0001) and group 2 ( P =0.002) after the guidance change vs before. Although ICU admissions increased significantly for children with BPD/CLDP in both group 1 ( P < 0.0001) and group 2 ( P =0.0004), use of MV ( P =0.002) increased after 2014 for children with BPD/CLDP in group 1 only. Similar results were observed for BH. Conclusion: This analysis highlights the increase in RSVH, BH, and associated severity among BPD/CLDP subgroups within the PHIS health system after 2014. Further study of long-term complications associated with RSVH in these children is warranted. Disclosures: Jaime Fergie, MD, AstraZeneca (Speaker's Bureau)Sobi, Inc. (Speaker's Bureau) Tara Gonzales, MD, Sobi, Inc. (Employee) Mina Suh, MPH, International Health, EpidStrategies (Employee) Xiaohui Jiang, MS, EpidStrategies (Employee) Jon Fryzek, PhD, MPH, EpidStrategies (Employee) Adam Bloomfield, MD, FAAP, Sobi, Inc. (Employee)